Respectful maternity care: a comparative exploration of mothers’ knowledge and experiences in Meghalaya - Devi, Gayatree; Myrthong, Catherine Eva; Kom, K. Rosema (International Journal Of Community Medicine And Public Health, 2025)
Background: Pregnancy and childbirth are vulnerable times for women, making respectful maternity care (RMC) essential to ensure safety, dignity, and autonomy. Despite global progress, mistreatment during childbirth remains common, affecting women’s healthcare choices. This study assessed mothers’ knowledge and experiences of RMC in selected healthcare facilities in Meghalaya, India, comparing urban and rural settings and exploring the link between their knowledge and experiences. Methods: A descriptive cross-sectional comparative study was conducted between January 15 and February 10, 2024, among 120 mothers in selected healthcare facilities. A structured questionnaire assessed knowledge, while the Indian person-centered maternity care scale evaluated experiences. Data analysis included descriptive statistics, independent t-tests, and correlation coefficients. Results: The study revealed that 65.8% of mothers had poor knowledge regarding respectful maternity care, with urban mothers showing significantly lower knowledge levels compared to rural mothers (p≤0.012). However, 86.7% of mothers reported positive experiences with respectful maternity care, with no notable difference between urban and rural mothers (p=0.287). A weak positive correlation (r=0.17) was identified between mothers’ knowledge and their experiences of RMC. Conclusions: The findings emphasize a knowledge gap regarding respectful maternity care among mothers, especially in urban areas, despite overall positive experiences. Increasing awareness and education on RMC is essential. Introducing ongoing quality improvement efforts and feedback systems in healthcare facilities can further strengthen respectful maternity care, ensuring the dignity and rights of all childbearing women are respected.